Factor influences celebrity in politics / Izzatur Nadhirah Abdul Aziz...[et al.] - Abdul Aziz, Izzatur Nadhirah; Hassan, Nur Afiqah Izzati; Noor Azmi, Serafina Amelia; Ramlan, Aini Faezah (Faculty of Communication & Media Studies, 2020)
Celebrity means a famous person especially in entertainment or sport. This study is made to see whether celebrity makes an impact and influence people into choosing which political parties. The questionnaires were made via Google Docs and spread through social medias. The study involved 400 respondents selected through a purpose sampling method involving 4 different stage of ages in Malaysia. A cross sectional survey and structured questionnaires were used for data collection. All variables were measured through scales previously used by other researchers. No software was used in the analysis. Results shows that people between the age of _____ tends to believe that educated celebrities do influence people easily (M = __) then popularity (M = __).